2022
DOI: 10.3390/molecules27196220
|View full text |Cite
|
Sign up to set email alerts
|

Integrated System Pharmacology Approaches to Elucidate Multi-Target Mechanism of Solanum surattense against Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignant liver tumors with high mortality. Chronic hepatitis B and C viruses, aflatoxins, and alcohol are among the most common causes of hepatocellular carcinoma. The limited reported data and multiple spectra of pathophysiological mechanisms of HCC make it a challenging task and a serious economic burden in health care management. Solanum surattense (S. surattense) is the herbal plant used in many regions of Asia to treat many disorders including vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Khalid et al [28] represented a multitarget network pharmacology approach to explore the mechanisms of S. surattense to target HCC. A molecular docking analysis revealed the potential of quercetin to inhibit the target proteins involved in the pathogenesis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Khalid et al [28] represented a multitarget network pharmacology approach to explore the mechanisms of S. surattense to target HCC. A molecular docking analysis revealed the potential of quercetin to inhibit the target proteins involved in the pathogenesis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…PPI analysis showed that AKT1, EGFR, SRC, ESR1, PPARG, PTGS2, MAPK3, GSK3B, MMP9, and PARP1 were key targets for PVL treatment of HCC. These key targets were mainly involved in biological processes such as HCC cell proliferation, apoptosis, cell cycle regulation, epithelial mesenchymal transition, tumor metastasis, and drug resistance (Khalid et al., 2022; Wang et al., 2017; Weng et al., 2023; Yun et al., 2022). KEGG analysis showed that PVL may block HCC progression via multiple pathways and biological processes including PI3K/Akt signaling.…”
Section: Discussionmentioning
confidence: 99%